Lead Exposure Causes Alteration of Haematological Indices in Adult Female Wistar Rats - I, Adeyomoye O; A, Adewumi N (Asian Journal of Pharmaceutical Research and Development, 2019)
Objective: Lead is a heavy metal widely distributed in the environment. It is known to be a toxicant and has no biological function. Humans are constantly exposed to lead from many sources and its effects on the haematological indices have not been fully elucidated. Therefore, this study aimed to investigate the changes in haematological profile of adult female Wistar rats exposed to lead. Design: Forty-five female Wistar rats with average weight of 150 ± 20g were randomly distributed into 3 groups of 15 rats each. Group 1 served as the control and was exposed to water only, group 2 was exposed to lead acetate (500mg/L) while group 3 was exposed to lead acetate (1000mg/L). The rats were exposed to lead for 52 days. On the 26th, 39th and 52nd days of exposure, five rats (n=5) were sacrificed from each group after mild anaesthesia and their blood samples were taken into EDTA bottles for haematological analysis using blood auto-analyzer. Results were analyzed using two-way ANOVA and p<0.05 were considered statistically significant. Main outcome measure: There was significant increase (p<0.05) in white blood cell and lymphocyte counts in 500mg/L and 1000mg/L lead exposed groups when compared to the control. There was significant decrease (p<0.05) in monocyte and granulocyte counts in 500mg/L and 1000mg/L lead exposed groups when compared to control group. Platelet counts significantly increased (p<0.05) in 500mg/L and 1000mg/L lead exposed groups when compared to control group. Conclusion: In conclusion, exposure to lead at 500 and 1000mg/L increased white blood cells, lymphocyte and platelet counts while it decreased monocyte and granulocyte counts in adult female Wistar rats. Therefore, lead at the exposed levels caused some alterations in the haematological parametersin adult female Wistar rats.